Using the completing-the-square method, rewrite f(x) = x^2-6x+2 in vertex form.
A f(x)= (x-3)^2
B f(x)= (x-3)^2 +2
C f(x)= (x-3)^2 -7
D f(x)= (x-3)^2 +9

Respuesta :

Answer:

Option C.  f(x)= (x-3)^2 -7

Step-by-step explanation:

we have

[tex]f(x)=x^2-6x+2[/tex]

step 1

Complete the square

Remember to balance the equation by adding the same constants to each side.

[tex]f(x)=(x^2-6x+3^2)+2-3^2[/tex]

[tex]f(x)=(x^2-6x+9)-7[/tex]

step 2

Rewrite as perfect squares

[tex]f(x)=(x-3)^2-7[/tex]

The vertex is the point (3,-7)

ACCESS MORE